The ballad and its pasts : literary histories and the play of memory - Atkinson, David, 1955 February 23- (D.S. Brewer, 2018)
The ballad genre, and its material, are frequently backward-looking in terms of subject and style: it is ideally suited to the reimagining of past events, both real and fictional. This volume addresses the past of the ballad and the past in the ballad. It challenges existing scholarship by embracing discontinuity rather than continuity, seeing the ballad as belonging to a culture of cheap print and imaginative literature rather than the rarefied construct of a mythical "folk". It finds a conscious antiquarianism and medievalism reinterpreting the genre at different stages of its literary history, at the same time as the ballad itself is continually adapting to the needs of readers, singers, and audience. Chapters cover the few remaining examples of the medieval ballad, and Thomas Percy's medievalism; David Mallet's "William and Margaret" and the beginnings of the gothic mode early in the eighteenth century; ballads of "Sir James the Rose" and the culture of cheap print in Scotland from the late eighteenth through to the early twentieth century; shipwreck ballads on the loss of the Ramillies and "Sir Patrick Spens", and the reimagining of the past in the present, with a diversion into Coleridge's "Dejection: An Ode"; murder ballads, special providence, and the history of mentalities from early modern to Victorian times.--